The Impact of Individual Online Platforms on Children’s Psychological Development - Gołuch, Dominik (Children in Digital Age, 2025)
Abstract:In the era of digitalisation, online platforms have become an integral part of the lives of children and young people, playing a key role in their educational, social, and emotional development. This study aims to describe the potential impact of online platforms on the development of young users while showing the benefits and potential risks associated with their use. On the positive side, access to a wide range of educational resources and opportunities for social interaction via the Internet can support learning and the development of communication skills. Simultaneously, attention has been drawn to challenges, such as the risk of addiction, cyberbullying, and sleep disorders, which may result from the excessive and uncontrolled use of digital technologies. This study also highlights the importance of the role of adults – parents, teachers, and legislators – in creating a safe digital environment that promotes healthy online habits. Digital education, establishing rules for using the Internet, promoting off-screen physical activities and hobbies, and developing critical thinking about Internet content are recommended. It is important that adults are aware of the potential risks and actively support young people in safely using the Internet while building trust and openness to dialogue about their online experiences. Although online platforms offer young users numerous development opportunities, a conscious and balanced approach to using them is required. By promoting healthy digital habits and actively engaging adults in the digital education process, we can ensure that the Internet becomes a safe and valuable tool that supports the comprehensive development of children and youth.Keywords: development of children and youth, online security, digital education, excessive use of the Internet, online platforms, healthy digital habits